Setting of some criteria for Piezoelectric Materials Stabilizability - BIDOUAN, Romziath; SENE, Abdou; MARCOS, ABOUBACAR (My University, 2023)
Ce travail est consacré a l’étude de la stabilisation d'un corps piézoélectrique soumis a un champ électromagnétique .
Keywords: Piezoelectric materials; Dielectrics; Electromagnetic.